Electrochemical Selective Oxidative Functionalization of Caffeine. Issue 5 (27th January 2020) - Liang, Xing‐An; Liu, Dingdong; Sun, He; Jiang, Chongyu; Chen, Hong; Niu, Linbin; Mahato, Karuna; Abdelilah, Takfaoui; Zhang, Heng; Lei, Aiwen
Abstract: Direct electrochemical oxidative functionalization of caffeine under metal‐free and external‐oxidant‐free conditions was achieved. Nucleophiles such as various substituted pyrazoles, alcohols, and sodium trifluoromethanesulfonate can be utilized with high diastereoselectivity for the dearomatizative functionalization of caffeine. In addition, selective C2 functionalization of caffeine has also been realized with the modification of solvent and reaction time. A gram‐scale experiment demonstrates the potential application in the derivatization of caffeine. Abstract :